Primitive neuroectodermal tumor of the uterine cervix diagnosed during pregnancy: A rare case with review of literature. Issue 3 (26th November 2013) - Khosla, Divya; Rai, Bhavana; Patel, Firuza D.; Sreedharanunni, Sreejesh; Dey, Pranab; Sharma, Suresh C.
Abstract Primitive neuroectodermal tumors of the cervix are very rare. A 28‐year‐old pregnant woman presented with a cervical mass. The tumor was staged as IB2. The biopsy from tumor was suggestive of malignant small round cell tumor. She then underwent termination of pregnancy followed by radical hysterectomy. Based on morphologic and immunohistochemical profile, a diagnosis of peripheral primitive neuroectodermal tumor of the cervix was made. The patient received adjuvant chemotherapy and radiotherapy. The patient is alive and disease‐free 33 months post‐surgery. The present case highlights the importance of keeping primitive neuroectodermal tumors in the differential diagnosis of small cell neoplasms of the uterine cervix. Pregnancy should not be a barrier to early detection and treatment of this potentially aggressive tumor. The optimal treatment methods have not yet been established because of the rarity of the tumor.